The Conservation on Indonesian Native Chicken Biodiversity Through Primordial Germ Cells Cryopreservation - Tribudi, Yuli Arif; Kostaman, Tatan (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
ABSTRACT Primordial germ cells (PGCs) can be cryopreserved and used as a potential tool for the preservation of poultry biodiversity. By transplanting donor PGCs into recipient embryos to produce chimera germline, PGCs can migrate to developing gonads where germ cells are produced, thus enabling reproduction of offspring derived from donor PGCs via mating of chimera germline. Collection of PGCs from the circulation of chickens. Fertile eggs were incubated in a portable incubator for 2.5 days. Purification of circulating PGCs with nycodenz. Then the PGCs were frozen using the 5% DMSO cryoprotectant and to determine the success of cryopreservation, the donor PGCs were transplanted into the recipient embryos. The number of circulating PGCs was 50.58 ± 5.79 cells per embryo, the percentage of PGCs viability after thawing was 80.18 ± 1.25%. From the results of the PGCs transplant by looking at the migration of donor PGCs in recipient embryos with PKH-16 staining, it is clear. In conclusion, PGCs cryopreservation in this study can generally support the survival of good chickens and it is hoped that this PGCs conservation protocol can be used for other native chickens.Keywords: PGC, cryopreservation, chicken, conservation